Pengaruh Penyajian Laporan Keuangan, Aksesibilitas, dan Komitmen Manajemen terhadap Transparansi Laporan Keuangan Pemerintah Daerah (Studi Kasus pada Satuan Kerja Perangkat Daerah (SKPD) Kota Bandung Tahun 2021) - Syilvia Tresnawati; Sri Rahayu (UNIVED Press, 2023)
This study aims to determine whether the presentation of financial statements, accessibility, and management commitment have a simultaneous and partial effect on the transparency of local government financial statements in the Bandung City Regional Apparatus Work Unit (SKPD) in 2021. This research is a type of descriptive and verifiable research. The population in this study is all heads and sub-sections of finance in SKPD Bandung City. The sample determination technique uses non-probability sampling with a total of 112 people. The data in this study were analyzed using a multiple linear regression method using IBM SPSS version 25 software. The results showed that the presentation of financial statements, accessibility, and management commitment had a simultaneous effect on the transparency of local government financial statements. Partially, only accessibility and management commitment have a positive effect on the transparency of government financial statements in the Bandung City Regional Apparatus Work Unit (SKPD) in 2021.